Cumulative Effects of Avian Predation on Upper Columbia River Steelhead. Issue 5 (18th September 2019) - Evans, Allen F.; Payton, Quinn; Cramer, Bradley M.; Collis, Ken; Hostetter, Nathan J.; Roby, Daniel D.; Dotson, Curtis
Abstract: To investigate the cumulative effects of colonial waterbird predation on fish mortality and to determine what proportion of all sources of fish mortality (1 − survival) was due to bird predation, we conducted a mark–recapture–recovery study with upper Columbia River steelhead Oncorhynchus mykiss that were PIT‐tagged and released ( N  = 78, 409) at Rock Island Dam on the Columbia River, USA. We used a state–space Bayesian model that incorporated live detections and dead recoveries of tagged fish to jointly estimate predation and survival probabilities during smolt out‐migration to the Pacific Ocean over an 11‐year study period. Estimated cumulative (all colonies combined) avian predation probabilities ranged from 0.31 (95% credible interval [CRI] = 0.27–0.38) to 0.53 (95% CRI = 0.42–0.64) annually, indicating that avian predation was a substantial source of mortality. Of the predator species evaluated, predation by Caspian terns Hydroprogne caspia was often the highest, with predation probabilities ranging from 0.11 (95% CRI = 0.09–0.14) to 0.38 (95% CRI = 0.29–0.47). Probabilities of predation by double‐crested cormorants Phalacrocorax auritus and mixed colonies of California gulls Larus californicus and ring‐billed gulls L. delawarensis were generally lower than the probabilities for terns but were also substantial, with upwards of 0.04 (95% CRI = 0.03–0.07; cormorants) and 0.31 (95% CRI = 0.25–0.39; gulls) of steelhead consumed. Comparisons of total smolt mortality with mortality due to avian predation indicated that avian predation accounted for 42% (95% CRI = 30–56%) to 70% (95% CRI = 53–87%) of total mortality, suggesting that more steelhead were consumed by avian predators than died from all other mortality sources combined. Results indicate that avian predation, although not the original cause of steelhead declines in the basin, is now a factor limiting the survival of upper Columbia River steelhead. Using the analytical framework developed in this study, future studies can consider the cumulative impact of multiple mortality sources across large spatial and temporal scales to more fully understand the extent to which they limit fish survival.